IMPLEMENTANSI MANGLE FILTERING CONTENT MENGGUNAKAN MIKROTIK UNTUK MENINGKATKAN KEAMANAN JARINGAN - Aldo Bonifasius Simbolon; Dean Siregar; Steven Adventino Gulo; Dedy Kiswanto (LPPM Universitas Dhyana Pura, 2025)
Network security is a crucial aspect that must be taken into account in information system management. This research focuses on implementing Mangle Filtering Content using MikroTik RB750 device to enhance network security. An experimental method with a case study approach was used to test the effectiveness of the mangle firewall feature in blocking unwanted content on local networks. The research was conducted by designing a simple network topology consisting of a MikroTik router as the traffic control center, one client device, and an internet connection. Mangle rules were implemented to mark connections based on specific domains and URL patterns through Layer-7 Protocol Filtering, then integrating the mangle results with Filter Rules to block access to unwanted sites such as social media and adult websites. The results showed that the implementation of mangle filtering content on MikroTik successfully blocked access to predetermined sites, creating a safer and more controlled digital environment. This research provides practical solutions for network administrators in improving security and digital content management on small to medium-scale networks.